Mythology Politik Jawa dalam Pidato Anas Urbaningrum (Analisis Semiotika Roland Barthes dalam Pidato Anas Urbaningrum Terkait Kasus Korupsi Hambalang) - Hani Yuniani (Jurnal Komunikasi, 2015)
Anas Urbaningrum received attention from the media lately because of his messages consisting multi interpretation statements through the analogy of puppet story. Anas' speech, which is driven on semiotics review, becomes an interesting topic for a research due to its connection with national politics reality and dynamic within this political year. The result of this research shows that Anas's message indicated Susilo Bambang Yudhoyono as the narrator/director of Hambalang case series. The Hambalang Project gratification case is a project prepared by SBY in order to overthrow Anas as the Chairman of Partai Demokrat that was legally gained. KPK becomes SBYs assistant to smoothen the operation and to prepare the plot. Demokrat Party still has no democratic tradition because of the strong feeling of aristocracy in the party’s internal body.